2021
DOI: 10.1101/2021.04.19.440462
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The association between Hfq and RNase E in long-term nitrogen starvedEscherichia coli

Abstract: The regulation of bacterial gene expression is underpinned by the synthesis and degradation of mRNA. In Escherichia coli, RNase E is the central enzyme involved in RNA degradation and serves as a scaffold for the assembly of the multiprotein complex known as the RNA degradosome. The activity of RNase E against specific mRNAs can also be regulated by the action of small RNAs (sRNA). The ubiquitous bacterial chaperone Hfq bound to sRNAs interacts with the RNA degradosome for the sRNA guided degradation of target… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The loss of an RNase E-mCherry signal in TIRF mode after chloramphenicol treatment strongly suggests that RNA degradosomes in the foci are not membrane attached. Recent work has shown that nitrogen starvation in E. coli triggers a stress response that results in the formation of foci containing RNA degradosomes and the RNA chaperone Hfq ( 63 , 64 ). By analogy, we propose that the foci formed by chloramphenicol treatment are part of a stress response induced by the inhibition of translation elongation.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of an RNase E-mCherry signal in TIRF mode after chloramphenicol treatment strongly suggests that RNA degradosomes in the foci are not membrane attached. Recent work has shown that nitrogen starvation in E. coli triggers a stress response that results in the formation of foci containing RNA degradosomes and the RNA chaperone Hfq ( 63 , 64 ). By analogy, we propose that the foci formed by chloramphenicol treatment are part of a stress response induced by the inhibition of translation elongation.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted April 1, 2022. ; https://doi.org/10.1101/2022.04.01.486790 doi: bioRxiv preprint 29 little is known about TmaR, this protein affects polar localization of enzymes of the phosphotransferase system (PTS) (55). Hfq can form polar foci under conditions of nitrogen starvation (56), raising the question of whether there is a connection between this phenomenon and the interaction between the GlnZ and tmaR RNAs. Conceivably further understanding of the GlnZ role in the regulation of these targets could give insights into the physiological response to low ammonium.…”
Section: Glnz Alters Metabolismmentioning
confidence: 99%
“…While 29 little is known about TmaR, this protein affects polar localization of enzymes of the phosphotransferase system (PTS) (55). Hfq can form polar foci under conditions of nitrogen starvation (56), raising the question of whether there is a connection between this phenomenon and the interaction between the GlnZ and tmaR RNAs. Conceivably further understanding of the GlnZ role in the regulation of these targets could give insights into the physiological response to low ammonium.…”
Section: Glnz Alters Metabolismmentioning
confidence: 99%